Plant diversity, structure and composition of vegetation around Barumun Watershed, North Sumatra, Indonesia - Ridahati Rambey; ARIDA SUSILOWATI; AHMAD BAIQUNI RANGKUTI; ONRIZAL ONRIZAL; DESRITA DESRITA; RIO ARDI; ADRIAN HARTANTO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rambey R, Susilowati A, Rangkuti AB, Onrizal O, Desrita, Ardhi R, Hartanto A. 2021. Plant diversity, structure and composition of vegetation around Barumun Watershed, North Sumatra, Indonesia. Biodiversitas 22: 3250-3256. Watershed ecosystem plays an important role in water and soil conservation which is supported by vegetation around watershed. As such, vegetation analysis is beneficial to assess the current state of watershed vegetation and monitor future changes. Barumun Watershed, located in South Labuhanbatu District, North Sumatra Province, Indonesia, is under threat due to habitat degradation and land conversion for plantation and agriculture. This research aimed to investigate the diversity, structure and composition of vegetation in the Barumun River including its smaller streams (rivulets). Data were collected using a combination of line transect and quadratic plots arranged systematically. The total observation plots were 48 plots, consisting of 24 plots in Barumun River, 12 plots in Tasik Rivulet and 12 plots in Titi Kembar Rivulet. The results documented a total of 51 plants in the studied sites in Barumun Watershed in which 37 species were found in Barumun River, 20 species in Tasik Rivulet and 17 species in the Titi Kembar Rivulet. Plant species consisted of several habitus including herbs, palms, shrubs, climbers and trees. The trees consisted of 22 species (43.13%), herbs 22 species (43.13%), climbers 3 species (5.88%), shrubs two species (3.92%), and palm two species (3.92%). The highest Importance Value Index (IVI) for tree community was recorded in the Barumun River from Hevea brasiliensis (108.28), followed by Cryptocarya sp. (123.24) in the Titi Kembar Rivulet. In addition, the highest IVI for pole, sapling, seedling, and shrub was recorded from Muntingia calabura (Barumun River), Nauclea orientalis (Tasik Rivulet), Psychotria viridiflora (Tasik Rivulet), and Calamus axillaris (Titi Kembar Rivulet), respectively. The plant diversity in Barumun Watershed was categorized from low to moderate level of richness.